KEANEKARAGAMAN JENIS BURUNG DI BEBERAPA TUTUPAN LAHAN DI SUAKA MARGASATWA MANEMBO-NEMBO - Rian S. Darwis; Reynold P. Kainde; Wawan Nurmawan (COCOS, 2020)
ABSTRACTThe purpose of this research is to be able to find out and analyze the diversity ofbird species in some land cover at Manembo-nembo Wildlife Reserve. Thisresearch was conducted in January-March 2020, a research location in theManembo-nembo Wildlife Reserve area which includes the administrative area ofSouth Minahasa Regency. The method used is the method of point count with thenumber of 7 points used as observation samples with each primary dry land forest3 points, dry land farming 3 points and dry land agriculture mixed with shrubs 1point. The data analysis used is (Shannon-Wiener Diversity Index), (RelativeAbundance Index), (Average Index) and (Type Similarity Index). The resultsshowed that there are 60 species of birds from 28 families in the Manembo-nemboWildlife Reserve in the South Minahasa adiministration region. This area has adiversity value (3.21) as an indicator of the high diversity of bird species. Forprimary dryland forest cover has a diversity index value (3.01) with a total of 34types, a value (2.97) with a total of 31 types on agricultural cover of dry landmixed with shrubs and the lowest value on dryland agricultural cover (2.77) witha total of 42 types.Keywords : Diversity of bird species, Land cover, Manembo-nembo WildlifeReserve